2014
DOI: 10.1007/s00114-014-1246-3
|View full text |Cite
|
Sign up to set email alerts
|

New parasitoid-predator associations: female parasitoids do not avoid competition with generalist predators when sharing invasive prey

Abstract: Optimal habitat selection is essential for species survival in ecosystems, and interspecific competition is a key ecological mechanism for many observed species association patterns. Specialized animal species are commonly affected by resource and interference competition with generalist and/or omnivorous competitors, so avoidance behavior could be expected. We hypothesize that specialist species may exploit broad range cues from such potential resource competitors (i.e., cues possibly common to various genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
0
18
1
1
Order By: Relevance
“…when the predator was already well established before arrival of T. absoluta or T. achaea releases began (Calvo et al , 2012 b ). Macrolophus pygmaeus (Rambur) (Heteroptera: Miridae), which is biologically comparable with N. tenuis , was also found to reduce effectiveness of T. achaeae against T. absoluta , but not at a greenhouse level (Chailleux et al , 2013, 2014 b ). Contrarily, Desneux et al (2010) found that supplementary releases of T. achaeae following release of N. tenuis after planting improved control of T. absoluta .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…when the predator was already well established before arrival of T. absoluta or T. achaea releases began (Calvo et al , 2012 b ). Macrolophus pygmaeus (Rambur) (Heteroptera: Miridae), which is biologically comparable with N. tenuis , was also found to reduce effectiveness of T. achaeae against T. absoluta , but not at a greenhouse level (Chailleux et al , 2013, 2014 b ). Contrarily, Desneux et al (2010) found that supplementary releases of T. achaeae following release of N. tenuis after planting improved control of T. absoluta .…”
Section: Discussionmentioning
confidence: 99%
“…species, which do not share a resource/habitat and/or seasonal occurrence (Northfield et al , 2012). N. tutae and N. tenuis attack different stages of T. absoluta (Urbaneja et al , 2009; Calvo et al , 2013), but they could interact negatively through: (1) Kleptoparasitism, the predator feeds on paralyzed host larvae or hostfed larvae by the parasitoid, what induces to ectoparasitoid larval mortality (Chailleux et al , 2014 b ); (2) ‘Unidirectional’ intraguild predation, the omnivorous predator feeds on parasitoid larvae directly; (3) Competition, either the predator or the parasitoid reduces future prey or host for the other.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that coexistence was possible between the two natural enemy species, despite the asymmetry in their diet breadth and the occurrence of kleptoparasitism (Chailleux, Wajnberg et al., ): S. japonicus and M. pygmaeus became successfully established in all treatments in which they were released and were present throughout the duration of the experiment. Nevertheless, for both biocontrol agent species, their population sizes were significantly lower when they were in competition with each other versus when they were alone.…”
Section: Discussionmentioning
confidence: 97%
“…It should be possible to use this parasitoid species through inoculative releases to control T. absoluta, although its capacity to persist in tomato crops in the presence of M. pygmaeus remains to be assessed. Moreover, mirid predators can exert kleptoparasitism and/or intraguild predation on T. absoluta larval parasitoids by feeding on paralyzed and parasitized host larvae or by directly attacking the juvenile parasitoids developing on the host larvae (Chailleux, Wajnberg, Zhou, Amiens-Desneux, & Desneux, 2014;Naselli et al, 2017). The objectives of this study were (i) to quantify the outcome of a frequent species association with an ecosystem (i.e., a specialist natural enemy and an omnivorous natural enemy), both feeding on the same prey, and (ii) to identify resource utilization patterns that could promote the coexistence of the two natural enemies.…”
mentioning
confidence: 99%
“…In contrast, other studies have shown avoidance of plants with con-or heterospecific competitors and intraguild predators based on volatiles emanating from these plants, both for predators (Janssen et al 1997;Gnanvossou et al 2003;Magalhães et al 2005;Maleknia et al 2013) and herbivores (Pallini et al 1997). Because of the limited attention given to such interactions, the are not yet well understood (Janssen et al 1997;Chailleux et al 2014).…”
Section: Discussionmentioning
confidence: 99%